(untitled) (Research, Society and Development, 2021)
The Child Health Handbook (CHH) was founded as a free means of visualization and surveillance of child growth and development, where the article aims to highlight the main challenges faced by nursing professionals in using the Health Handbook for the diagnosis of children with ASD. This is a bibliographic research of the integrative literature review type, consisting of a qualitative, integrative, exploratory and descriptive research. As for the results, professionals have great difficulty in handling the child’s health booklet, finding themselves unprepared to effectively monitor the child’s health. There are numerous benefits of using early intervention in children with autism spectrum disorder, including: Better cognitive development and greater learning, reduced stress for the child and family, and greater social interaction. In this aspect, the need for nursing professionals to identify or collaborate to identify these children is highlighted. Therefore, there is a need to instruct professionals and the community about the benefits of using CHH, in addition to carrying out more research in this line of investigation to prove the importance of special attention to children’s health.